Dye-Sensitized Solar Cells with Cost-Effective Counter Electrode Based on Soybean Oil Lampblack - Lawaju, Umesh; Joshi, Prakash (Journal of Nepal Physical Society, 2022)
We have used soybean oil lampblack as a low-cost counter electrode (CE) material to replace expensive platinum in dye-sensitized solar cells (DSCs). The lampblack was prepared by obstructing the flame of the soybean oil lamp with a porcelain bowl and characterized with the techniques of X-ray diffraction (XRD) and Raman spectroscopy for structural analysis and scanning electron microscopy for surface morphology. The XRD of the lampblack indicated the presence of graphitic carbon in the lampblack while Raman spectroscopy of the carbonaceous material disclosed that the lampblack consists of both disordered and ordered forms of carbon. The lampblack was used with printer toner to prepare counter electrodes (CEs) of DSCs. The scanning electron microscopy of the film of the lampblack with toner showed that the toner serves as a binder to hold the particles of the lampblack on the CEs. The catalytic ability of the CEs was evaluated with electrochemical impedance spectroscopy (EIS). The charge transfer resistance Rct at the toner-electrolyte interface determined by EIS was extremely high (5.32 x 105 Ωcm2 ). Similarly, Rct at the carbon-electrolyte interface and platinum-electrolyte interface were 13.46 Ωcm2 and 2.29 Ωcm2 , respectively. The DSCs based on soybean oil lampblack achieved the light to electric energy conversion efficiency (η) of 2.58% and the platinum based solar cell achieved η of 3.67%.